Randomized controlled trial on Pringle Maneuver to reduce blood loss during stapler hepatectomy - PriMal StHep - Houben, Philipp; Hinz, Ulf; Knebel, Phillip; Diener, Markus K.; Mehrabi, Arianeb; Schemmer, Peter (BMC surgery, 2019)
Extended liver resections still bear the risk of severe haemorrhage. Moreover, the amount of blood loss during liver resection determines the need for perioperative blood transfusions and is of prognostic relevance in oncologic surgery. Even though there is an ongoing debate about its effectiveness and tolerable duration, the Pringle Maneuver (PM) as an occlusion of the hepatic inflow is routinely applied to reduce blood loss during parenchymal dissection. In combination with the stapler resection technique, PM is expected to minimize blood loss during major liver resection safely due to the short parenchymal dissection duration.
Gesehen am 01.08.2019